2020
DOI: 10.2215/cjn.16011219
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Daprodustat Compared with Darbepoetin Alfa in Japanese Hemodialysis Patients with Anemia

Abstract: Background and objectivesDaprodustat is an oral hypoxia-inducible factor prolyl hydroxylase inhibitor that stimulates erythropoiesis and regulates genes related to iron metabolism. The efficacy (noninferiority) and safety of daprodustat compared with standard therapy (darbepoetin alfa) was evaluated.Design, setting, participants, & measurements This was a randomized, phase 3, double-blind, active-control study in Japanese patients receiving hemodialysis with anemia of CKD. Participants’ treatment was switc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(124 citation statements)
references
References 16 publications
6
96
1
Order By: Relevance
“…Among Japanese hemodialysis patients who received ESA treatment, death and cancer progression were not reported during the 52-week study period. 28 Among the adverse events reported in ≥5% of patients per group, contusion and diarrhea were reported ≥5% more frequently in the daprodustat group than in the darbepoetin alfa group. Similar to a phase 2 study, 25 the incidence of hyperkalemia was reported in the daprodustat group (3%) compared to the darbepoetin alfa group (1%).…”
Section: Adverse Effectsmentioning
confidence: 92%
See 3 more Smart Citations
“…Among Japanese hemodialysis patients who received ESA treatment, death and cancer progression were not reported during the 52-week study period. 28 Among the adverse events reported in ≥5% of patients per group, contusion and diarrhea were reported ≥5% more frequently in the daprodustat group than in the darbepoetin alfa group. Similar to a phase 2 study, 25 the incidence of hyperkalemia was reported in the daprodustat group (3%) compared to the darbepoetin alfa group (1%).…”
Section: Adverse Effectsmentioning
confidence: 92%
“…Akizawa et al conducted a 52-week, randomized, double-blind, phase 3 study to assess the noninferiority of daprodustat in maintaining the hemoglobin level among Japanese hemodialysis patients and its safety compared to darbepoetin alfa (NCT02969655). 28 Every participant received a stable dose of ESA treatment (darbepoetin alfa 10–60 µg/week, epoetin (including biosimilars) ≤9000 IU/week, or epoetin beta pegol up to 250 µg/4 weeks) at least 10 weeks before screening. Among 271 patients, 136 were randomized, receiving 4 mg daprdodustat with dose titration every 4 weeks based on a prespecified algorithm to achieve or maintain the target hemoglobin level (10–12 g/dl).…”
Section: Therapeutic Clinical Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other reports showed that daprodustat increased Hb in a dose-dependent manner in HD patients whose pretreatment average Hb value was less than 10 g/dL, and the secondary analysis showed that VEGF remained unchanged and the endogenous EPO concentration was within a physiological range (maximum EPO concentration < 50 mIU/mL). As for ESA resistance, Akizawa et al found that darbepoetin-αrDA), compared to daprodustat, required a broader range administration dose, suggesting that the ESA hyporesponsiveness is better controlled in the daprodustat-treated group [69]. In addition, there was basically no difference in the PK and the PD between Caucasian and Japanese with a slightly high AUC in the latter, which may be originated from the difference in body size [70].…”
Section: Characteristics Of Hif Stabilizersmentioning
confidence: 99%